Konsep Pembaharuan Pendidikan Islam Versi Jamaluddin Al-Afghani - Rizadiliyawati, Rizadiliyawati; Roza, Ellya (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
The aim of this research is to analyze Jamaluddin Al-Afghani's Version of the Concept of Islamic Education Reform. This type of research is a library study. Data collection with documentation. Data analysis with SLR. The research results obtained are that Jamaluddin Al-Afghani's version of the concept of Islamic education renewal is that Islamic education must continue to develop according to the needs of the times and can be integrated with modern science. Afghani emphasized the importance of education that fosters a critical, innovative and progressive spirit in thinking and promotes universal human values. Through its progressive and inclusive approach, Afghani advocates for Islamic education to play an active role in preparing individuals to face global challenges and strengthen Islamic civilization in the contemporary context.